Matsubara-Fradkin thermodynamical quantization of Podolsky electrodynamics - Bonin, C. A. [UNESP]; Pimentel, B. M. [UNESP] (Amer Physical Soc, 2011)
In this work, we apply the Matsubara-Fradkin formalism and the Nakanishi's auxiliary field method to the quantization of the Podolsky electrodynamics in thermodynamic equilibrium. This approach allows us to write consistently the path integral representation for the partition function of gauge theories in a simple manner. Furthermore, we find the Dyson-Schwinger-Fradkin equations and the Ward-Fradkin-Takahashi identities for the Podolsky theory. We also write the most general form for the polarization tensor in thermodynamic equilibrium.